2022
DOI: 10.1186/s40538-022-00328-w
|View full text |Cite
|
Sign up to set email alerts
|

Shared phytochemicals predict efficacy of essential oils against western flower thrips (Frankliniella occidentalis) in the greenhouse

Abstract: Western flower thrips (Frankliniella occidentalis; Thysanoptera: Thripidae), or WFT, are a global pest of commercial crops, particularly those grown in greenhouses. Current management recommendations often involve judicious use of pesticides to which WFT have evolved multiple resistance phenotypes. Essential oils (EOs) have shown promise as a less toxic alternative for WFT greenhouse management. However, challenges remain in predicting which EOs are most likely to be insecticidal to WFT and ensuring that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Indeed, PSG was effective in controlling WFT in the ingestion, contact and greenhouse assays in this study. More recently, Durr et al [ 10 ] observed that essential oils of peppermint, fir, arborvitae and thyme were effective in reducing a greenhouse WFT population relative to a water control. We hypothesize that mineral oil causes a variety of effects, including “arrested activity” in WFT with a repellent effect that discourages egg disposition and feeding, consequently making it effective even at low concentration, as found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, PSG was effective in controlling WFT in the ingestion, contact and greenhouse assays in this study. More recently, Durr et al [ 10 ] observed that essential oils of peppermint, fir, arborvitae and thyme were effective in reducing a greenhouse WFT population relative to a water control. We hypothesize that mineral oil causes a variety of effects, including “arrested activity” in WFT with a repellent effect that discourages egg disposition and feeding, consequently making it effective even at low concentration, as found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cyantraniliprole is a registered pesticide in Canada and the US, with no WFT resistance reported to date, although Wang et al [ 24 ] have reported WFT resistance to cyantraniliprole in China. WFT use detoxification enzymes including cytochrome P-450 monooxygenases, and P450s have been confirmed as a key factor in the initial development of cyantraniliprole resistance by Aphis gossypii Glover and field-evolved resistance in Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) [ 10 , 25 , 26 ]. It is therefore possible that thrips’ resistance to cyantraniliprole will continue to increase and spread geographically, intensifying the need for alternatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations